2011
DOI: 10.1007/s00394-011-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin regulates organic ion transporter and uromodulin expression and improves renal function in hyperuricemic mice

Abstract: These results suggest that quercetin has the uricosuric and nephroprotective actions mediated by regulating the expression levels of renal organic ion transporters and UMOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 57 publications
3
41
1
Order By: Relevance
“…Experimental results first demonstrated that core ingredients in MSW could protect HUVECs by reducing cell apoptosis and inhibiting expression of ICAM-1 in MSU-induced HUVECs for antiacute gout. Besides, these ingredients such as Quercetin, Resveratrol, Palmitic acid, Astilbin, down-regulated hepatic XOD and enhanced renal urate excretion in hyperuricemic mice by up-regulating OAT1 and down-regulating URAT1 and GLUT9 mRNA and protein levels in the kidney (Wang and Sweet, 2012;Hu et al, 2012). Researches confirm that various ingredients in MSW are effective for gouty treatment by targeting inflammatory cytokines and UA synthetas or transporters through different related pathways, which indicates a whole regulation with the paradigm of "multi-ingredient, multitarget, multi-pathway".…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results first demonstrated that core ingredients in MSW could protect HUVECs by reducing cell apoptosis and inhibiting expression of ICAM-1 in MSU-induced HUVECs for antiacute gout. Besides, these ingredients such as Quercetin, Resveratrol, Palmitic acid, Astilbin, down-regulated hepatic XOD and enhanced renal urate excretion in hyperuricemic mice by up-regulating OAT1 and down-regulating URAT1 and GLUT9 mRNA and protein levels in the kidney (Wang and Sweet, 2012;Hu et al, 2012). Researches confirm that various ingredients in MSW are effective for gouty treatment by targeting inflammatory cytokines and UA synthetas or transporters through different related pathways, which indicates a whole regulation with the paradigm of "multi-ingredient, multitarget, multi-pathway".…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that OAT (Sekine et al , ; Wang et al , ; Hu et al , ) plays an important role in the renal excretion of urate. Therefore, the concentration of uric acid can be affected by the consumption of tea not only by its inhibition of XO (Table ) but also its interaction with OAT (Table ).…”
Section: Interaction With Transportersmentioning
confidence: 99%
“…Dysregulation of transport activity could potentially lead homeostatic imbalance and uric acid accumulation. In fact, previous studies indicate that plant derivatives with antioxidant activities like quercetin and nuciferine ameliorate OA‐induced hyperuricemia by regulating the expression of some uric acid transporters. Along similar lines, the observed systemic and mitochondrial anti‐hyperuricemia effect of Tq may therefore be ascribed to alterations in transcriptional patterns of such transporters.…”
Section: Discussionmentioning
confidence: 99%